Failure of trypanocidal drugs to cure trypanosome infections in cattle in Boundiali District, northern Cote d'Ivoire - Coulibaly, L.; Hecker, P.A.; Krebs, H.A.; Rowlands, G.J.; D'Ieteren, G.D.M.; Leak, S.G.A.; Peregrine, A.S.; Nagda, S.M. (OAU/STRC, 1995)
Twelve traditional herds of cattle in the area of Boundiali, northern Cote d'Ivoire, were examined monthly from 1990 to 1992 for the presence of trypanosomes. The herds were randomised into 3 treatment groups, cattle in 4 herds received diminazene aceturate at 3.5 or 7 mg/kg body weight (b.w.) when detected parasitaemic; cattle in 4 herds received isometamidum chloride at 0.5 or 1 mg/kg when detected parasitaemic; and cattle in 4 herds homidium bromide at 1 mg/kg when detected parasitaemic. Thirty one percent of 236 cases that were parasitaemic and treated were parasitaemic at the next month's sample when treated with diminazene aceturate or within two months when treated with isometamidium chloride or homidium bromide. This percentage was much higher than the monthly incidence of new infections (mean 4 percent, 85 percent of infections T. vivax, 15 percent T. congolense) and suggested that approximately 27 percent of infections may have been drug resistant. Some animals continued to be detected parasitaemic over several months. In order to relate the number of detected parasitaemias to the number of spearate individual infections. an estimated new infection was defined as a case of parasitaemia preceded by at least two months without detection of the same species of trypanosome. The infections were then examined to determine the proportion that may have recurred. There were no significant differences in rates of recurrence of infection among the three drugs (20/68 (29 percent) for diminazene aceturate, 15/39 (38 percent) foor isometamidum chloride, and 18/62 (29 percent) for homidium bromie) or between different doses for each drug. However, when cattle greater than 36 months of age were compared with those less than 36 months of age, the mean treatment failure rate in the older cattle was half that in younger cattle (22 percent and 41 percent, respectively; x2=8.1, P<0.01). This implies that the overall failure rate of the drugs to cure infections presumably due to drug resistance, was compensated to some extent by an acquired immunity to trypanosomal infections as the animals grew older.